2017
DOI: 10.1002/chem.201604966
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Molecular Photoswitches Based on Overcrowded Alkenes for Dynamic Control of Catalytic Activity in Michael Addition Reactions

Abstract: The emerging field of artificial photoswitchable catalysis has recently shown striking examples of functional light-responsive systems allowing for dynamic control of activity and selectivity in organocatalysis and metal-catalysed transformations. While our group has already disclosed systems featuring first generation molecular motors as the switchable central core, a design based on second generation molecular motors is lacking. Here, the syntheses of two bifunctionalised molecular switches based on a photor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 90 publications
0
22
0
9
Order By: Relevance
“…[ 76 ] Recently, they developed the second‐generation molecular motor to construct a new artificial stimulus‐response chiral catalytic system. [ 77 ] Unlike the first‐generation molecular motor, the second‐generation molecular motor has different metastable states during the rotation process. They introduced the biphenyldiol unit into the molecular switch and found that the chiral center could induce the helical chirality of the molecular switch.…”
Section: Allosteric Catalysts Based On Single Moleculesmentioning
confidence: 99%
“…[ 76 ] Recently, they developed the second‐generation molecular motor to construct a new artificial stimulus‐response chiral catalytic system. [ 77 ] Unlike the first‐generation molecular motor, the second‐generation molecular motor has different metastable states during the rotation process. They introduced the biphenyldiol unit into the molecular switch and found that the chiral center could induce the helical chirality of the molecular switch.…”
Section: Allosteric Catalysts Based On Single Moleculesmentioning
confidence: 99%
“…Bifunctional molecular photoswitches based on the overcrowded alkene scaffold found in the so-called second generation molecular motors 41 have been recently investigated as light-responsive catalysts. 42 Photoresponsive thioureas 27 were synthesised in both E and Z forms, which showed efficient photoisomerisation upon irradiation with 312 nm light (Scheme 13). However, the photogenerated metastable states (M)-Z-27 and (M)-E-27 did not show reversible photoisomerisation upon irradiation with 365 nm light as happens in the unfunctionalised counterparts.…”
Section: Activity Controlmentioning
confidence: 99%
“…The cooperation of thiourea and tertiary amine in cis states was found a key factor for stereoselectivity of Henry reaction of nitromethane and fluorinated ketones and Michael reaction of bromonitrostyrene and pentanedione. Bisfunctional, photoswitchable, dual stereoselective catalysts based on the idea of unidirectional molecular motors were designed by Feringa and co-workers (Figure 28) [330,331]. The cooperation of thiourea and tertiary amine in cis states was found a key factor for stereoselectivity of Henry reaction of nitromethane and fluorinated ketones and Michael reaction of bromonitrostyrene and pentanedione.…”
Section: Thioureas and Bis-thioureas With Axial Planar Or Helical Chiralitymentioning
confidence: 99%